Human Resource Management in Islamic Boarding Schools: The Leadership Roles of Tuan Guru, Ustaz, and Foundation Leaders in Achieving Sustainable Islamic Educational Governance - M. Sahidi (Indonesian Journal of Education and Science, 2025)
Islamic boarding schools (pondok pesantren) are vital institutions for religious and moral education in Indonesia, where leadership and human resource management (HRM) play a crucial role in sustaining educational quality. This study aims to conduct a systematic literature review on HRM practices in pesantren, focusing specifically on the leadership roles of Tuan Guru, Ustaz, and foundation leaders in promoting sustainable Islamic educational governance. Using a qualitative descriptive approach, the research analyzed 25 peer-reviewed articles published between 2019 and 2024. Thematic content analysis was used to identify patterns in HRM components, leadership contributions, and governance outcomes. The findings reveal five core HRM components commonly applied in pesantren: value-based recruitment, performance appraisal aligned with Islamic ethics, continuous professional development, organizational culture grounded in trust and justice, and structured career pathways. Leadership from Tuan Guru, Ustaz, and foundation leaders significantly influences transparency, staff engagement, and quality assurance. However, challenges such as limited leadership training, resistance to change, and digital illiteracy persist. This study provides a comprehensive framework integrating Islamic leadership values with modern HRM practices and highlights the need for leadership development and digital capacity-building in pesantren. It offers theoretical and practical insights for scholars and stakeholders aiming to strengthen educational governance in Islamic institutions.